Retirement village in Malaysia case study: Sri Seronok Retirement Village (Cheras) Darussolihin Pensioners Home (Kuala Nerang) Pondok Hidayatullah (Sitiawan) / Fasihah Mohamed Noordin - Mohamed Noordin, Fasihah (2010)
Senior citizens refer to individuals who are over 60 years old. Since 1960's, there have been an increasing number of senior citizens in Malaysia because of the reduction in child birth and mortality rates, improvement in controlling infectious diseases and better medical facilities. The increasing of life span has caused the accumulation of the elderly. With this enlargement, it is actually to show and remind us about necessity and responsibility toward social welfare, care and protection as well as to provide a better life for senior citizens. In the context of provision and planning for specific accommodations for senior citizens, it is a continuous process and understanding must exist toward individual needs, interest, and aspiration. This study is about the importance of retirement village where it is the accommodation for senior citizens which is still new in Malaysia. Its development in Malaysia is less in number based on the lack of exposure given to Malaysian society. Thus, this study was conducted to identify the retirement village. Moreover, the study was also conducted pertaining to the concept of retirement village. This study explored through theoretical and empirical by looking to the approach and concept or experiences in western countries in the development of retirement village. The experiences in western countries have approved that their society and government are very concerned about how important it is to provide shelter and accommodation that are more comfortable for senior citizens. Furthermore, the study was conducted on the community of retirement village to identify its development nowadays fulfil the senior citizens' needs. From the study, an effective and practical approach in the form of recommendations was structured to cope with the weaknesses. In addition, it could be a basic or guideline for development planning of retirement village to make it more comfortable in the future.